Comparative study of foreign investment laws: The case of China and Ghana - Ayangbah, Shirley (Cogent social sciences, 2017)
This article provides a comparative legal study of some relevant features of the Chinese and Ghana Foreign Investment Laws (FIL), keeping in mind the differences in both countries constitutions and legal systems. Ghana is comparatively more developed, socially and economically, than other countries in sub-Saharan Africa and as such perceived by other scholars and foreign investors as a suitable place for foreign investments partly due to a suitably educated workforce, cheap labor costs and it natural resources. However, the effect of the foreign investments in accelerating the development of the country is a concern though the government seeks to attract gigantic foreign investment, which is also regarded as a possible solution to the mounting current account shortage problem. On the other hand, China has shown a reliable flow in FDI influxes in spite of its economic slowdown and marked legal reforms in current years. Are there available lessons for Ghana from the advantages (and shortcomings) of the Chinese Foreign Investment Regulation? Of course, Yes, Ghana can definitely learn from China’s “national investment policy-making,” though the benefits derived from this comparative study can be mutual.